Cross-Dynastic Intergenerational Altruism - Frikk Nesje (Center for Economic Studies and ifo Institute (CESifo), 2022)
I study whether saving behavior reveals socially relevant intertemporal preferences. To this end, I decompose the present generation's preference for the next into its dynastic and cross-dynastic components in a model of saving. If people are concerned about the next generation as such, then they might assign welfare weights on other dynasties. With such cross-dynastic intergenerational altruism, saving for one's descendants benefits present members of other dynasties. These preference externalities imply that socially relevant intertemporal preferences cannot be inferred from saving behavior. Numerically, I show that even " preferences for the next generation as such can lower the efficient discount rate by 20% to 40%, as compared to Nordhaus' calibration.
Keywords: D64; D71; H43; Q01; Q54; 330; intergenerational altruism; social discounting; time-inconsistency; declining discount rates; generalized consumption Euler equations; interdependent utility; isolation paradox